LncRNA-ANCR regulates the cell growth of osteosarcoma by interacting with EZH2 and affecting the expression of p21 and p27 - Fei Zhang; Hao Peng (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background Osteosarcoma (OS) is one of the most common malignant tumors developed in the bone. EZH2 has been found to play pivotal roles in the development of various cancers. LncRNA-ANCR (anti-differentiation ncRNA) has been reported to interact with EZH2 and regulated osteoblast differentiation. Our study aimed to investigate the effect of lncRNA-ANCR on the tumorigenesis of osteosarcoma and explore the underlying molecular mechanism. Methods RT-PCR was performed to detect the messenger RNA (mRNA) levels of lncRNA-ANCR, EZH2, p21, and p27 in OS tissues and cell lines. The cell proliferation, transwell invasion, and migration assays were conducted to evaluate the influence of lncRNA-ANCR depletion on the growth of OS cells. RNA pull-down assay was carried out to detect the interaction between lncRNA-ANCR and EZH2. Correlation between the expression of lncRNA-ANCR and the expression of EZH2 were analyzed by cross-tabulation. Results LncRNA-ANCR is highly expressed in both OS tissues and cell lines. Reduced expression of lncRNA-ANCR inhibited the cell proliferation, invasion, and migration of OS cells. The cell apoptosis rate was also increased with the overexpression of lncRNA-ANCR. Mechanistically, downregulation of lncRNA-ANCR reduced the mRNA level of EZH2 and increased the expression of p21 and p27 at both mRNA and protein levels. LncRNA-ANCR interacted with EZH2 and their expression abundance was positively correlated in OS patients. Conclusion LncRNA-ANCR inhibited the cell proliferation, migration, and invasion of OS cells possibly through interacting with EZH2 and regulating the expression of p21 and p27.